Fístula enterocutánea sigmoideo umbilical como rara complicación de una diverticulitis del colon sigmoide - Brito Sosa, Germán; Iraizoz Barrios, Ana María (My University, 2022)
The care of patients with enterocutaneous fistula constitutes a significant challenge owing to the alterations it usually brings about. For successful treatment, it is necessary to manage fluids and electrolytes adequately, provide practical nutritional support, and control sepsis until its eradication; thus, many fistulae close spon - taneously. We present the case of a 36-year-old male patient with a four-month history of fecal-like umbilical secretion. When performing the fistulogram, we confirmed a fistulous tract of 9 cm, which ended at the level of the sigmoid colon, a rare location. In cases where the enterocutaneous fistula does not close, and surgical treatment is indicated, it is imperative to maximize perioperative care, decrease surgical time, choose the correct surgical technique, and prepare the patient for surgery to avoid complications with a fatal outcome.
La atención de los pacientes con fístula enterocutánea constituye un gran reto, por las alteraciones con las que suelen acompañarse. Para lograr un tratamiento exitoso es necesario realizar un adecuado manejo de los líquidos y electrolitos, brindar un apoyo nutricional eficaz y controlar la sepsis hasta lograr su erradicación; de esta manera, muchas fístulas cierran espontáneamente. Se expone el caso de un paciente de 36 años de edad, con un cuadro de secreción umbilical de aspecto fecaloideo de 4 meses de evolución. Al realizar la fistulografía se constató un trayecto fistuloso de 9 cm, el cual terminaba a nivel del colon sigmoide, localización poco frecuente. En los casos en que la fístula enterocutánea no cierre y tenga indicación de tratamiento quirúrgico, es necesario extremar los cuidados perioperatorios, minimizar el tiempo quirúrgico, elegir la técnica quirúrgica correcta y preparar al paciente para la cirugía, de modo que se eviten complicaciones que pueden tener un desenlace fatal.
Keywords: FISTULA DEL SISTEMA DIGESTIVO; DOLOR ABDOMINAL; COLON; SIGMOIDE